ANTI-INFLAMMATORY AND ANTICANCER POTENTIAL OF SALSOLA KALI L. AGAINST SKIN CANCER IN ALBINO RAT MODEL - HAMEED , A; MUGHAL , TA; GHANI , N; NAEEM , I (Biological and Clinical Sciences Research Journal, 2024)
In the realm of cancer treatment, plants are offering effective curative compounds and most of the anticancer compounds have been obtained from the plants. Salsola kali L. is an important ethnomedicinal plant of the Chenopodiaceae family. In folkloric healthcare practices, it is being used to treat skin diseases. In the current study, plant extracts were prepared in solvents of different polarities through soxhlation and subjected to the detection of potential bioactive metabolites through Fourier Transform Infrared Spectroscopy and Gas Chromatography-Mass Spectrometry. The anti-inflammatory efficacy of plant extract was also determined through carrageenan and histamine assays. The anticancer potential of the plant was tested against the cancerous skin of albino mice. The studied plant had encouraging anti-inflammatory efficacy. The carrageenan percent inhibition occurred in a dose-response manner and peak edema volume reduction occurred at 4 hr. Findings of the carrageenan assay were also confirmed with the histamine assay. At 120 min maximum edema inhibition was detected and inflammation was reduced upto 65%. Animal study on rats, presented S. kali L. as a potential local biological resource for skin cancer treatment. Chemotherapy of animals with n-Hexane extract showed excellent results in curing benign lesions. Squamous cell carcinoma in situ and malignant fibrous hyperplasia were cured mildly, and malignancy progression did not occur. Plant extract’s anticancer activity also coincided with the presence of potent bioactive compounds that were recorded in IR-spectra; triterpenoid and glycosidic saponins as O-H, C=O, C-H and C=C and C-O groups, respectively. Ethyl acetate also had good efficacy against the skin lesions. However, methanol extract showed less outcomes. GC-MS analysis of n-Hexane extract revealed the presence of an anticancer epoxide Cis-2.3-Epoxycotane. Ethyl acetate extract also showed the presence of an anticancer carbohydrate 1,6-Dideoxy-1-mannitol. These two anticancer compounds have been reported in the literature as having cancer cure potential. Further, after cytotoxic analysis studied plant may be proven as a potential chemotherapeutic resource for skin cancer treatment.